Labeling of the Recombinant Streptokinase Using Iodine-131 as a New Thrombolytic Agent - I. Daruwati; A. Hanafiah; D.S. Retnoningrum; H. Rachmawati (PPIKSN-BATAN, 2012)
Stroke and acute myocardial infarction is a disease with the highest mortality in the world. WHO has estimated in 2008, 30% of deaths from heart disease and more than 80% of this cases have been occurred in developing countries. Streptokinase (SK) as an effective thrombolytic agent has been used as a drug of choice for about forty years ago. SK is plasminogen (PG) activator that converts plasminogen to active protease, called plasmin (PN) which degrades fibrin to soluble products. Recombinant streptokinase (SKA) from genetic engineering has been developed at School of Pharmacy ITB to reduce or eliminate immunogenicity of SK. However, scientific disclosures relating to dynamic and its kinetic studies in the body have still to be proven. One method that can explain this phenomenon is the pharmacological studies using radionuclide labeled compounds. Radioiodine labeled compound is used extensively and most suitable for biological studies. This paper describes the preparation of 131I-SKA and its characterization. The labeling conditions of SKA, such as chloramine-T as an oxidizing agent, amount of SKA, incubation time, and size of resin to purify the labeling yield have been observed. The result showed that the optimum condition of labeling (35.11%) was obtained using 10 µg of chloramine-T and 60 seconds of incubation time. The highest radiochemical purity (97.46 ± 1.14%) has also been obtained by passing through the resin chromatography column using 100 mg Dowex 1x8, size 50-100 mesh. The characterization of 131I-SKA with SDS PAGE method and autoradiography showed the similar performance with unlabeled-SKA.Received: 04 December 2012; Revised: 20 December 2012; Accepted: 21 December 2012